Acupuncture: a traditional chinese medicare - Pathan, ANM Fazlul Haque (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
DOI: http://dx.doi.org/10.3329/jbsa.v24i1.19797 Journal of Bangladesh Society of Anaesthesiologists 2011; 24(1): 28-33